ON THE ROUTE OF DERISION AND COURSE: THE PORTUGUESE INTERNET SERIES BICHA DO DEMONIO - Valentim, Jorge Vicente [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2018)
This essay aims to read the Portuguese internet series Bicha do Demonio (2009-2010), produced exclusively for dissemination on the network by Youtube, taking as a starting point the presence of a satirical vein, observed under two aspects: the first, while continuity of a literary and cultural tradition of derision and evil saying; and the second, as a direct exposition of sexual subjectivities, as well as the multiplicities of the Portuguese homosexual universe.
Keywords: derision; course; intertextuality; Portuguese culture; Bicha do Demonio